What exactly is wrong and why? Tutorial Dialogue for Intelligent CALL Systems - Klenner, Manfred; Visser, Henriëtte (Linguistik Online, 2003)
We introduce a dialogue-based explanation facility for Intelligent CALL (ICALL) Systems. Our prototype system, DiBEx, uses meta reasoning to build up an explanation (error) tree, given a faulty user input. It relies on correct grammatical subtheories, instead of explicit error taxonomies. DiBEx, thus, realizes anticipation free error diagnosis. The system enters in a tutorial dialogue with the student, where each explanation (dialogue) step is based on the principles of a single tutorial strategy and a dynamic user model.